EPISTEMOLOGI TARBAWI GEN Z: REKONTEKSTUALISASI KONSEP TABAYYUN DAN AHL AL-DZIKR SEBAGAI FILTER HOAX DAN KRISIS OTORITAS - Rohman, Fatkhur; Ali, Muhammad Haidir; Arifin, Achmad Zainul; .Abdurrahman, Abdurrahman (Kreatif: Jurnal Pemikiran Pendidikan Agama Islam, 2026)
Generation Z is now facing a paradox in lifelong learning activities. While they have access to a wealth of information, they are also surrounded by the threat of hoaxes and the uncertainty surrounding scientific authority due to the dominance of influencers. It has been proven that relying solely on technical digital literacy skills is insufficient to solve this fundamental problem. This study offers a solution: re-examining the values of Islamic education (tarbawi) in the Qur'an and Hadith as a foundation of knowledge for the digital generation. Using a qualitative approach based on a literature study, this research thoroughly analyses QS. Al-Hujurat: 6 and QS. An-Nahl: 43. This analysis uses a thematic and analytical approach, referring to Tafsir Al-Mishbah by M. Quraish Shihab and supporting Hadith literature. The results of the study show that: (1) tabayyun is not only about checking facts; it is also a behavioural approach that encourages restraint on social media, and (2) the synergy between the concept of ahl al-dzikr and the principle of sanad results in digital sanad logic: a method of assessing the veracity of knowledge based on the credibility of the expert rather than its popularity. The study concludes that integrating these two values is crucial in providing Generation Z with an internal filter to help them grow into critical and original learners.